2020
DOI: 10.20473/jr.v4-i.3.2018.71-75
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Radiografi Tuberkulosis Paru Multidrug-Resistant: Studi Retrospektif di Rumah Sakit Umum Dr. Soetomo Surabaya

Abstract: Background: Multidrug-resistant pulmonary tuberculosis (MDR-TB) is a major health problem worldwide. Prompt diagnosis is necessary for insuring appropriate therapy to lower morbidity and mortality, as well as to prevent disease transmission. Determination of drug-resistance patterns through microbiological examination is sometimes challenging, especially when the sputum acid-fast bacilli smear is negative. Therefore, it is worthwhile to investigate whether there may be radiographic patterns suggesting MDR-TB i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Radiological imaging has a role in screening and supporting MDR pulmonary TB diagnosis. A study by opacity/consolidation with bilateral lung involvement 3 .…”
Section: Multidrug-resistant/rifampicinmentioning
confidence: 99%
“…Radiological imaging has a role in screening and supporting MDR pulmonary TB diagnosis. A study by opacity/consolidation with bilateral lung involvement 3 .…”
Section: Multidrug-resistant/rifampicinmentioning
confidence: 99%
“…Radiological imaging has a role in screening and supporting MDR pulmonary TB diagnosis. A study by Sulaiman et al in 2018 regarding chest x-ray findings in pulmonary MDR-TB at Dr. Soetomo General Hospital, Surabaya, reported that pulmonary MDR-TB patients mostly had severe lesions, with the most frequent finding were ground-glass opacity/consolidation with bilateral lung involvement 3 .…”
Section: Multidrug-resistant/rifampicinmentioning
confidence: 99%